2010
DOI: 10.1016/j.drugpo.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Why don’t out-of-treatment individuals enter methadone treatment programmes?

Abstract: Background-Despite the proven effectiveness of methadone treatment, the majority of heroindependent individuals are out-of-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 45 publications
6
120
1
2
Order By: Relevance
“…24 Numerous other studies have confirmed the persistence of negative attitudes towards methadone and their impact on treatment recruitment and retention. 11,12,[25][26][27][28][29] Research has also shown that patients taking methadone are often hesitant to inform family members, employers, and physicians of their enrollment in treatment due to perceived stigma. 30 Such stigma and negative beliefs about methadone can lead to underutilization of a highly effective treatment modality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Numerous other studies have confirmed the persistence of negative attitudes towards methadone and their impact on treatment recruitment and retention. 11,12,[25][26][27][28][29] Research has also shown that patients taking methadone are often hesitant to inform family members, employers, and physicians of their enrollment in treatment due to perceived stigma. 30 Such stigma and negative beliefs about methadone can lead to underutilization of a highly effective treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…Examining how buprenorphine is viewed from the user's perspective -both as a pharmacological agent and as a service delivery model -is critical for understanding the decision processes underlying their treatment selection. Based on our previous research on treatment entry and engagement, [8][9][10][11][12][13][14][15][16][17][18][19] we hypothesized that patients would choose buprenorphine treatment due to its perceived advantages over methadone in patient burden (e.g. ability to receive takehome medication more quickly, fill prescriptions at a regular pharmacy, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…As yoga practice is a mainstream recreational activity in the United States, particularly among educated middle-class Whites (Birdee et al, 2008), their integrating postprison MBI recovery with societal reintegration will be a far less stigmatizing experience and administrative burden than what daily trips to the local methadone clinic tend to provoke (Gryczynski et al, 2011;Peterson et al, 2010). That is not to discount that regardless of race, formerly incarcerated individuals under community supervision must negotiate a host of reentry challenges.…”
Section: Mindfulness-based Interventions 1971-presentmentioning
confidence: 99%
“…The barriers included a long waiting list, lack of health insurance, fear of side effects of methadone, and various requirements in the registration procedure [15].…”
Section: Institutional Factorsmentioning
confidence: 99%